Mansfield Park. - Austen, Jane, 1775-1817 (Open Road Media, 2016)
A shy young woman discovers her true power in this poignant love story from one of the world's most cherished authors The eldest of nine children born to a naval lieutenant with a meager pension, Fanny Price is sent to live with wealthy relatives at Mansfield Park. Only ten years old, she is nervous around her rich cousins and uncomfortable in their grand house. And as the years pass, Fanny comes to believe that she will never truly feel at home. Only Edmund Bertram makes life worth living. He is the only one of her cousins who is kind to her, a gentle soul whom she has loved since childhood. But when the worldly and charismatic Crawford siblings, Henry and Mary, arrive from London and ensnare the Bertram family in a complicated web of romance and intrigue, Fanny worries that her relationship with Edmund will never be the same. To win his heart, she must keep her head--a task that becomes all the more difficult when her family pressures her to accept Henry Crawford's unexpected marriage proposal. Widely regarded to be Jane Austen's first mature novel, Mansfield Park subtly critiques the snobbery of English society by celebrating the virtues of its unassuming yet profoundly compelling heroine. This ebook has been professionally proofread to ensure accuracy and readability on all devices.